Investigation of Stepnogorsk city population residing near uranium processing plant - Zhumadilov, K.Sh.; Ivannikov, A.I.; Stepanenko, V.F.; Skvortsov, V.G.; Toyoda, S.; Hoshi, M. (Recent Contributions to Physics, 2017)
In the article the results of an estimation of possible excess of the absorbed dose received by workers of uranium-processing plant are included. The possible excess of dose of workers was evaluated with comparison with population set (Stepnogorsk) and control set (Astana city). All measured tooth enamel samples were extracted according to medical recommendations. Totally 27 tooth enamel samples were analyzed from the residents of Stepnogorsk city (180 km from Astana city, Kazakhstan). 6 tooth samples were collected from the workers of uranium processing plant. The results of 6 tooth enamel dose estimation show us a slight influence of working conditions to workers, the maximum excess dose is less than 100 mGy. The emergency (excess) doses of processing plant workers turned out to be lower than the doses of the population of Stepnogorsk city and the doses of residents of Astana city. This is pilot study of tooth enamel EPR dose estimation and for a final conclusion additional sample is required.